A glutathione-responsive ferroptotic inducer with elevated labile iron pool and self-supplied peroxide for chemodynamic therapy - Penghui Wei; Xuegang Niu; Dengliang Wang; Chengzhong Du; Mingtao Zhu; Hongjia Zheng; Yongrui Hu; Yu Tian; Wei Huang; Chengyu Ding; Yuanxiang Lin; Yang Zhu; et al. (Materials Today Bio)
Chemodynamic therapy (CDT) is a novel approach in the treatment of tumors in which ferrous iron (Fe2+) is the primary catalyst of the Fenton reaction. However, Fe2+ is typically stored in an oxidized mineral form as ferric iron (Fe3+) in ferritin, significantly limiting the efficacy of CDT. This work describes the preparation of redox-responsive nanoparticles (MO@DSSP NPs) embedded with OSMI-1 and methyl linoleate hydroperoxide (MLH) to synergistically enhance CDT efficacy, optimize peroxide supply and deplete glutathione (GSH). The redox-responsive MO@DSSP NPs undergo disintegration after being internalized by tumor cells due to the reductive tumor microenvironment, consuming GSH while releasing OSMI-1 and MLH. This process increases the intracellular labile iron pool (LIP) and oxidative stress at the tumor site by inhibiting O-GlcNAcylation of ferritin heavy chain (FTH). Furthermore, obstructing O-GlcNAc modification triggers mitochondrial fragmentation alongside autophagy, thus contributing an extra source of reactive iron. The increased LIP significantly promotes the generation of hydroxyl radical (·OH) that causes lipid peroxidation, consequent damage of the cell membrane and ferroptosis. Therefore, this study describes an attractive CDT nanoagent that effectively inhibits the O-GlcNAcylation of FTH to mobilize endogenous Fenton-type metals, as well as offers a basis to the exploration of LIP-activatable MLH with high CDT efficacy, demonstrating significant potential for clinical applications.